Pemberdayaan Ekonomi Masyarakat Berbasis Potensi Lokal terhadap Peningkatan Ekonomi Rumah Tangga - Adhistian, Patria; Ruspendi, Ruspendi; Aprina, Budi; Candra, Adi; Wahyu, Wahyu (LPPM Universitas Pamulang, 2020)
Village tourism is one of the community empowerment programs to maximize the potential of a village to improve the welfare of its people. Data collection techniques are done by interview, observation, and study of documents. Community empowerment is done by optimizing the village tourism program to be a tourism commodity based on the local potential of the community so that the household economy of the local community can improve. Untung Jawa tourism village has provided a change for the community especially in increasing the knowledge and economy of the community. Therefore the community empowerment program in the Tourism Village can be used as a reference in other community empowerment activities. Continuous Development Improving the Quality of Human Resources in Facing Global Competition as a Tourism Area, Community-Based Economic Empowerment on Local Potential Against Household Economic Improvement. The development of community-based tourism objects or community based tourism is the concept of developing a tourist destination through the empowerment of local communities, where the community contributes to the planning, management, and voting in the form of decisions in its development. The purpose of community empowerment assistance to local potential is to provide assistance for the creation and utilization of local potentials in improving the economy.